x2 + 8x + 15 = (x + 3)(x + 5)
x² + 8x + 15 = (x + 5)(x + 3)
2x^2 + 8x + 3 = 0
x2 - 8x + 15 = 0 can be factored as (x - 3)(x - 5) = 0 : This holds true when one or both of the terms in brackets equals zero. When x - 3 = 0 then x = 3 When x - 5 = 0 then x = 5.
X2 + 8x + 16 = 10x +16x2 + 8x + 16=2x + 8x + 16=10x + 16
x2 + 8x + 15 = (x + 3)(x + 5)
x2 + 8x + 15 = (x + 3) (x + 5).
x2-8x+15 = (x-3)(x-5)
no
x2 + 8x = -15 x2 + 8x + 15 = 0 since 15 = 5 x 3 and 5 + 3 = 8, then (x + 5)(x + 3) = 0 x + 5 = 0 or x + 3 = 0 x = -5 or x = -3
In general, no.
x² + 8x + 15 = (x + 5)(x + 3)
(-4,-1)
x2+8x+9 = -7 x2+8x+9+7 = 0 x2+8x+16 = 0 (x+4)(x+4) = 0 Therefore: x = -4 and also x = -4 (they both have equal roots)
x=-0.7
2x^2 + 8x + 3 = 0
x2 + 8x - 6 = 0 x2 + 8x + 16 = 22 (x + 4)2 = 22 x + 4 = ± √22 x = -4 ± √22